Filsafat Isyraqi Suhrawardi - A Khudori Soleh (UIN Sunan Kalijaga Yogyakarta, 2011)
Isyraqi or isyraqiyah (illuminative) is the thought developed by Suhrawardi al- Maqtul by integrating between the teachings of Sufism and philosophy. In detail, according to Hussein Nasr, isyraqi is based on five sources of thought that are Sufism, Islamic pariphatetic philosophy, pre-Islamic philosophy, the wisdom of ancient Iran, and the teachings of Zoroaster. The main doctrine essentially consists of two concepts, namely gradation of essence and self-awareness. The first concept relates to the ontological question, while the second relates to the epistemological question. From both concepts then born third teachings, mitsâl nature, in which the ontological structure of spiritual reality or ‘high nature’ is seemed to have a likeness or take forms in concrete picture of matter nature or 'lower nature'.